Salivary gland pathology in the paediatric population: implications for management and presentation of a rare case. (10th February 2014) - Jablenska, L; Trinidade, A; Meranagri, V; Kothari, P
Abstract: Introduction: Salivary gland pathology in the paediatric population is rare and can present management challenges regarding both investigation and treatment. Method: Case report and review of available literature. Results: A seven-year-old, fit, well girl presented with a two-month history of a painless mass over the left parotid area. Ultrasonography confirmed the presence of a well-defined, 1.5 × 2 cm, predominantly solid lesion with minor internal cystic spaces arising from the superficial part of the gland. Magnetic resonance imaging showed no invasion of the deep lobe or skeletal erosion. Superficial parotidectomy was performed via a facelift incision. Histopathology confirmed a diagnosis of pleomorphic adenoma. Review of the literature emphasised important differences in managing this pathology in the paediatric population when compared with adults. Conclusion: We present the youngest reported case of a pleomorphic adenoma of the parotid gland, detail its management, and discuss the general approach to parotid pathology management in the paediatric population.